Development and validation of an impedance biosensor for point-of-care detection of vascular cell adhesion molecule-1 toward lupus diagnostics. (7th July 2017) - Selvam, Anjan Panneer; Wangzhou, Andi; Jacobs, Michael; Wu, Tianfu; Mohan, Chandra; Prasad, Shalini
Aim: Systemic lupus erythematosus is an autoimmune disease that requires chronic monitoring. In this study, we demonstrate a proof-of-concept study of a highly attractive noninvasive strategy for monitoring systemic lupus erythematosus through biomarker quantification.Results: This sensor technology requires 50 μl of urine to detect and quantify vascular cell adhesion molecule-1 in 15 min. The sensor used nonfaradaic detection to demonstrate performance with and without detection antibody. Binding of immunoassay and target biomarkers were quantified with an impedance electrical immunoassay and correlated with an equivalent circuit.Conclusion: The novel sensor technology demonstrates detection in the range of 8 fg/ml to 800 pg/ml and comparative analysis with ELISA platforms was performed for 12 patient urine samples. Lay abstract: A proof-of-concept portable biosensing system for rapid screening of systemic lupus erythematosus through the use of a biomarker has been demonstrated. This sensor is an electronic urine test, which screens for vascular cell adhesion molecule. The efficacy of the sensor has been validated using a small cohort of patient urine samples that have been evaluated using standard clinical methods. This biosensor is the first demonstration of a consumer-friendly point-of-care test suitable for home monitoring.